2019
DOI: 10.1108/lht-02-2019-0042
|View full text |Cite
|
Sign up to set email alerts
|

The context and state of open source software adoption in US academic libraries

Abstract: Purpose The purpose of this paper is to identify barriers and drivers to open source software (OSS) adoption, and measures awareness and adoption stages of OSS in US academic libraries. Design/methodology/approach An online survey of chief information officers, chief technology officers or heads for IT in US academic libraries was conducted. A total number of 179 responses were used for data analysis. Findings From the survey, the authors identify significant barriers and drivers that US academic libraries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 32 publications
(61 reference statements)
0
13
0
Order By: Relevance
“…Sherikar and Jange (2006) stated that many librarians consider OSS because of its low buying costs as it has no initial purchase fees, licensing fees, or upgrade fees compared to proprietary software. Choi (2021) found the low cost, possibility to tailor to your library's specific needs, avoidance of vendor lock-in, ability to download and test the software in advance, greater flexibility and functionality of OSS, and independence from suppliers in choosing support and maintenance, as the drivers to OSS adoption while lack of staffing to maintain OSS, lack of technical expertise to implement and customize OSS, lack of employees who possess an understanding of OSS and assist its introduction, concern over receiving support, concern over the compatibility of OSS with the current systems, prior investments in proprietary software, concern over the quality of OSS, as the prominent issues that the public libraries consider in adopting OSS.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Sherikar and Jange (2006) stated that many librarians consider OSS because of its low buying costs as it has no initial purchase fees, licensing fees, or upgrade fees compared to proprietary software. Choi (2021) found the low cost, possibility to tailor to your library's specific needs, avoidance of vendor lock-in, ability to download and test the software in advance, greater flexibility and functionality of OSS, and independence from suppliers in choosing support and maintenance, as the drivers to OSS adoption while lack of staffing to maintain OSS, lack of technical expertise to implement and customize OSS, lack of employees who possess an understanding of OSS and assist its introduction, concern over receiving support, concern over the compatibility of OSS with the current systems, prior investments in proprietary software, concern over the quality of OSS, as the prominent issues that the public libraries consider in adopting OSS.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, according to Choi (2021), limited research has been conducted in the context of OSS in public libraries compared to academic libraries. Based on the literature, the study identified a few research studies that have been carried out in Sri Lanka focusing on OSS adoption in public libraries.…”
Section: Introductionmentioning
confidence: 99%
“…Studies suggested the reasons behind using open source software are free distribution, the possibility of customization, and free from regular payment for the software license. Yet, the huge setback for applying open-source software is the lack of own experts available in the libraries (Choi & Pruett, 2019). It is rare to find in-house experts available in the case of Nepalese libraries.…”
Section: Population Of the Studymentioning
confidence: 99%
“…With the increased interest in OSS among libraries, a great deal of research attention has also been devoted toward various OSS topics in the library setting (Choi, 2021). However, there had been a lack of effort to review prior literature on OSS in the library field.…”
Section: Introductionmentioning
confidence: 99%